An introduction to medical Spanish : communication and culture - Chase, Robert O., 1955-; Medina de Chase, Clarisa B., 1963- (Yale University Press, 2019)
"The updated, fifth edition of the widely used introductory Spanish textbook designed specifically for health care professionals As the Spanish-speaking population grows, nurses, doctors, dentists, and other health care professionals increasingly need to communicate in Spanish with their patients. Formerly titled An Introduction to Spanish for Health Care Workers, the fifth edition of this popular textbook is designed for students with little or no formal background in the language, and uses text, audio, video, classroom activities, and electronic exercises to teach basic grammar, specialized medical vocabulary, and colloquial terms as well as Latino customs and communication styles. The only program on the market with online videos demonstrating doctor-patient interactions, the fifth edition has been updated to include: High-frequency vocabulary lists; New activities to support the presentational mode of communication; Additional structure and lexicon related to zika, diabetes, pediatrics, heart disease, and neurological evaluation; A more interactive website with self-correcting exercises and supplemental material"--Provided by publisher